The Xenopus model as a tool for investigating craniofacial developmental disorders - Kong, Qianying; Peng, Huifang; Zhao, Qian; Jiang, Hongwei; Zhu, Xuechen (Frontiers in Medicine, 2025)
Normal craniofacial development depends on the precise specification, migration, and differentiation of cranial neural crest cells (CNCCs). Perturbations in these processes result in a wide spectrum of congenital craniofacial anomalies, which represent a major cause of birth defects worldwide. Xenopus has emerged as a particularly powerful model for investigating craniofacial morphogenesis, owing to its external fertilization, large and experimentally accessible embryos, and evolutionarily conserved developmental pathways. These advantages allow direct in vivo visualization and manipulation of CNCCs behaviors at single-cell resolution, providing opportunities not readily achievable in mammalian models. With the integration of advanced techniques such as high-resolution imaging, lineage tracing, microsurgical manipulation, and genome editing, the utility of Xenopus in craniofacial biology has been greatly expanded. In this review, we outline the key stages of craniofacial development, summarize representative craniofacial developmental disorders studied using Xenopus as a model, and highlight how this system has provided critical mechanistic insights. Importantly, the amenability of Xenopus embryos to small-molecule screening underscores their translational potential as a rapid preclinical platform, linking human genetic variants to disease pathogenesis and accelerating therapeutic discovery for craniofacial disorders, as well as its translational potential as a rapid preclinical platform, linking human genetic variants to disease pathogenesis and accelerating therapeutic discovery for craniofacial disorders.